2011
DOI: 10.1111/j.1365-2222.2011.03798.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of Der p 10: a diagnostic marker for broad sensitization in house dust mite allergy

Abstract: SummaryBackground-Tropomyosins represent clinically relevant seafood allergens but the role of mite tropomyosin, Der p 10, in house dust mite (HDM) allergy has not been studied in detail.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
77
2
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(86 citation statements)
references
References 39 publications
5
77
2
2
Order By: Relevance
“…Sensitization rates to Der p 10 between 10 and 18% in Austria up to 55% in Zimbabwe were reported in the literature [9][10][11]. As Austria directly borders to the southern Bavarian part of Germany and eating habits with mainly meat and less seafood diet is common, we expected a comparable sensitization to tropomyosin of above 10%.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Sensitization rates to Der p 10 between 10 and 18% in Austria up to 55% in Zimbabwe were reported in the literature [9][10][11]. As Austria directly borders to the southern Bavarian part of Germany and eating habits with mainly meat and less seafood diet is common, we expected a comparable sensitization to tropomyosin of above 10%.…”
Section: Discussionmentioning
confidence: 56%
“…Weghofer et al [9] found sensitization rates of 9% in France, 10% in Italy and 18% in Austria and Sweden. Comparable results for Austria of 15% could be shown by Resch et al [10]. Westritschnig et al analyzed sensitization proWles of African people in Zimbabwe and compared it with data from central Europe.…”
Section: Introductionmentioning
confidence: 80%
“…mite bodies or mite culture) [19,32]. The contents of Der p 1 and 2 have been well investigated in allergen extracts [21,32], but no studies have been performed to investigate mite extracts regarding other important allergens such as Der p 5, 7, 10 and 21 [5,25,26,34,35]. We found that certain of these allergens were absent in 8 of the 10 extracts studied.…”
Section: Discussionmentioning
confidence: 84%
“…The recombinant allergens rDer p 5, 7, 10 and 21 were expressed in the vector pET 17b as nonfusion proteins [ [5,25,26 ]and Casset and Vrtala, unpubl.]. rDer p 2 was expressed in the vector pET 17b with a C-terminal hexahistidine tag [27] and an rDer p 14 fragment (aa 1–260) was expressed in the vector pET 19b with an N-terminal hexahistidine tag [28].…”
Section: Methodsmentioning
confidence: 99%
“…Further profiling of allergen-binding patterns, as Simpson et al [34] suggest, could be informative within their newly defined risk categories. It has been shown that the 15% of European HDM-allergic subjects with IgE to the tropomyosin Der p 10 bind more HDM allergens [35], so ongoing investigations are warranted. With the spread of HDM allergy into developing regions [36], patterns of sensitisation that are not adequately represented by current HDM extracts could emerge.…”
Section: Discussionmentioning
confidence: 99%